PROJECT MANAGEMENT TEACHING AND TRAINING EXPERIENCE - Alfred. A. Dulzon (Высшее образование в России, 2022)
The main defects of traditional teaching and training in project management are discussed.It is shown that acquirement of project management methodology even on elementary levelis possible only through participation in team work and performance of a real project. Teaching techniques and the methodology of individual’s contribution estimation by team work are exposed.